The complete chloroplast genome sequences of nine melon varieties (Cucumis melo L.): lights into comparative analysis and phylogenetic relationships - Hu, Jianpeng; Yao, Jinchen; Lu, Jimei; Liu, Weiwei; Zhao, Zhiqiang; Li, Yaqian; Jiang, Lu; Zha, Liangping (Frontiers in Genetics, 2024)
Melon (Cucumis melo L.) is one of the most extensively grown horticulture crops of the world. Based on the morphological characters, melon was formerly divided into two subspecies, C. melo ssp. melo and C. melo ssp. agrestis. However, the present methods are still inadequate to distinguish between them. The phylogenetic analysis based on chloroplast genome sequences could provide essential evidence for the classification of melon varieties. We sequenced and analyzed the chloroplast genomes of nine different melon varieties. The results showed that the melon chloroplast genome has a typical quadripartite structure that was conserved across the analyzed sequences. Its length ranges between 155, 558 and 156, 569 bp, with a total GC content varying from 36.7% to 37%. We found 127-132 genes in melon chloroplast genomes, including 85-87 protein-coding regions, 34-37 tRNA and 6-8 rRNA genes. The molecular structure, gene order, content, codon usage, long repeats, and simple sequence repeats (SSRs) were mostly conserved among the nine sequenced genomes. Phylogenetic analysis showed that the chloroplast genome could clearly distinguish between C. melo ssp. melo and C. melo ssp. agrestis. This study not only provides valuable knowledge on melon chloroplasts, but also offers a theoretical basis and technical support for the genetic breeding of melons.